Investigating the infant gut microbiota in developing countries: worldwide metagenomic meta‐analysis involving infants living in sub‐urban areas of Côte d'Ivoire. Issue 5 (21st June 2021) - Fontana, Federico; Mancabelli, Leonardo; Lugli, Gabriele Andrea; Taracchini, Chiara; Alessandri, Giulia; Longhi, Giulia; Anzalone, Rosaria; Viappiani, Alice; Famo, Roch; Brognan, Marc; Micondo, Kouamé Hervé; Turroni, Francesca; et al.
Abstract: In recent decades, infants' gut microbiota has aroused constant scientific interest, primarily due to early‐ and long‐term repercussions on the host health. In this context, nutritional challenges such as those found in less developed countries can influence infants' gut microbiota development, thus generating potentially critical health outcomes. However, comprehensive investigations regarding species‐level differences in the infant gut microbiota's composition between urbanized and rural countries are still missing. In this study, 16S rRNA and Shallow Shotgun metagenomics sequencing were exploited to dissect the microbial community's species‐level composition of 11 faecal samples collected from infants living in a semi‐urban area of Sub‐Saharan Africa, i.e. Côte d'Ivoire. Moreover, the generated data were coupled with those retrieved from public available metagenomic repositories, including two rural communities and 13 urban communities of industrialized countries. The meta‐analysis led to the identification of Infant Species Community States Type (ISCSTs) and microbial species covariances, which were exploited to reveal key signatures of infants living in rural and semi‐urban societies. Remarkably, analysis of rural and semi‐urban datasets revealed shifts from ISCSTs prevalent in urbanized populations with putative health implications. Thus, indicating the need for population‐wide investigations aimed to define the factors determining such potentially harmful gut microbial communities' signatures.